Pengembangan Media Pembelajaran MUTA (Monopoli Ular Tangga) dalam Pembelajaran Matematika Materi Operasi Hitung Bilangan Bulat - Herlin Fajriah; M. Jaya Adi Putra; Syahrilfuddin (Jurnal Riset Pendidikan Dasar Dan Karakter, 2022)
This research is a development research to produce learning media in the form of MUTA (monopoly snake and ladder) game on integer arithmetic operations using the guessing method. The purpose of this development research is to develop a media game "MUTA" which is valid to be used as a medium for learning Mathematics for grade IV elementary school students in learning materials for multiplication and division counting operations. This type of research is development research using a 4-D model (define, design, development, and dissemination). The results of this study were obtained from the results of product feasibility validation from media expert validators and media content expert validators which stated that the "MUTA" game media product as a Mathematics learning medium for elementary school students developed by the researcher was very valid to be used with an average percentage gain. from media expert validators by 91.66% and content expert validators by 85%. For the teacher response test, the average percentage was 92.86% with a very decent category. To test the student's response to the "MUTA" game media product, it was done by giving a student response questionnaire sheet to 8 fourth grade students. From the results of the student response sheets that were distributed, an average percentage of 90.70% was obtained with the acquisition of a very decent category.